Foreign Direct Investment, Information Technology and Total Factor Productivity Dynamics in Sub-Saharan Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2022)
Compared to other regions of the world, the potential for information technology penetration in sub-Saharan Africa (SSA) is very high. Unfortunately, productivity levels in the region are also very low. This study investigates the importance of information technology in influencing the effect of foreign direct investment (FDI) on total factor productivity (TFP) dynamics. The focus is on 25 countries in SSA. Information technology is measured with mobile phone penetration and internet penetration, while the engaged TFP productivity dynamics are TFP, real TFP, welfare TFP, and real welfare TFP. The empirical evidence is based on the Generalised Method of Moments. The findings show that, with the exception of regressions pertaining to real TFP growth for which the estimations do not pass postestimation diagnostic tests, it is apparent that information technology (i.e. mobile phone penetration and internet penetration) modulate FDI to positively influence TFP dynamics (i.e. TFP, welfare TFP, and welfare real TFP). Policy and theoretical implications are discussed.
Keywords: E23; F21; F30; L96; O55; 330; Productivity; Foreign Investment; Information Technology; Sub-Saharan Africa